Molecular Analysis of Host Immune Responses to the Resident Colonic Microflora - B Bahrami; GT Macfarlane (Tehran University of Medical Sciences, 2005)
Ulcerative colitis (UC) is an idiopathic inflammatory bowel disease that affects the colonic mucosa. UC results from loss of tolerance towards the normal gut microbiota, leading to chronic mucosal inflammation. UC is incurable, and current therapies involve the use of immunosuppressant and anti-inflammatory drugs, steroids, and in extreme cases, surgery. UC treatments have a number of limitations, and can induce non-specific suppression of the host immune response, resulting in undesirable side effects, while having little effect on mucosal bacterial populations that are involved in disease aetiology. Manipulation of the composition of the microbiota to change mucosal cytokine profiles, by probiotics, may provide an alternative therapy. In vitro modeling was used to investigate the induction of immuno-modulatory cytokines in two human epithelial intestinal cell lines, Caco2 and HT-29. The cells were co-cultured for 3 and 8 hours with a range of mucosal bacteria: Clostridium clostridiiforme, Enterococcus faecalis, Escherichia coli, Lactobacillus paracasei, Peptostreptococcus anaerobius, and Bifidobacterium bifidum, Bif. longum, Bacteroides fragilis, Bact. thetaiotamicron and Bact. vulgatus. Quantitative real-time PCR assays for the cytokines interleukin-4 (IL-4), -10, -18 and transforming growth factor beta-1 (TGFb-1), -2, -3 were developed, and used to assess cytokine gene expression. Results were normalised for cell number against b-actin and GAPDH. High basal levels of IL-18 mRNA were detected in both cell lines. Caco2 expressed higher levels of TGFb_isoforms than HT-29 cells. Peptostreptococcus anaerobius, Bact. vulgatus and Bif. longum up-regulated IL18 in HT-29, whereas Bact. fragilis and Bact. thetaiotamicron down-regulated this cytokine. All bacterial isolates down-regulated IL-18 mRNA levels in Caco2, and all bacterial isolates except Bact. fragilis and Bact. thetaiotamicron significantly up-regulated TGFb-1. There was little change in expression of IL-4, IL-10, TGFb-2 and TGFb-3. Caco2 had higher baseline levels of cytokine mRNA, compared to HT-29. Mucosal bacteria induced a higher level of immune response in HT-29 than Caco2. This could be because the phenotype of HT-29 cells is that of crypt epithelial cells, which in healthy mucosa, do not normally encounter live bacteria. In a situation of chronic inflammation, these nascent epithelial cells respond to bacterial challenge by producing immuno-modulatory cytokines. In contrast, the more mature Caco2 cells are in constant contact with commensal bacteria and their products and have evolved to tolerate antigenic challenges, and maintain homeostasis. Accurate and reliable assays for the use of quantative rtPCR to investigate gene expression levels of human immuno-modulatory cytokines have been developed. Experimental evidence provided a working hypothesis regarding the abilities of different commensal organisms to trigger the immune system, and re-establish healthy immune status. Further studies to tailor potential immune modulating probiotic species for the treatment of individual UC patients, based on this hypothesis, are currently in progress.